2015
DOI: 10.1109/tgrs.2015.2403957
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of ZY-3 Optical Sensors

Abstract: As the first Chinese civilian high-resolution remotesensing satellite, Ziyuan 3 (ZY-3) is equipped with nadir, forward, and backward cameras for stereo mapping. In order to acquire high-resolution mapping accuracy, in-orbit sensor calibration is a particularly crucial procedure after the satellite is launched and orbiting. The key problem of in-orbit sensor calibration is analyzed based on the overall structural design and imaging geometric characteristics of ZY-3. In this paper, a rigorous imaging model of ZY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In addition, practical and repeatable comparative analyses of the Landsat-7/ETM+ and the Landsat-8/OLI were conducted by Peng et al [22] from spectral bands and vegetation indices, and the results showed that the two sensors had high similarity (the R 2 was greater than 0.96) though subtle differences existed. Therefore, the ETM+ and OLI imagery can be used as complementary data [23].…”
Section: Oli Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, practical and repeatable comparative analyses of the Landsat-7/ETM+ and the Landsat-8/OLI were conducted by Peng et al [22] from spectral bands and vegetation indices, and the results showed that the two sensors had high similarity (the R 2 was greater than 0.96) though subtle differences existed. Therefore, the ETM+ and OLI imagery can be used as complementary data [23].…”
Section: Oli Imagerymentioning
confidence: 99%
“…The primary characteristics of the ZY-3 are listed in Table 3. The applications of the ZY-3 data are primarily cartography, DEM modelling and resource investigation [3,23,28]. Obviously, the DEM extracted by the ZY-3/TLC has a higher spatial resolution and is more suitable for the cross-calibration of the GF-1/WFV than the ASTER GDEM.…”
Section: Dem Extracted By Zy-3/tlcmentioning
confidence: 99%
“…As a relatively new optical system, the ZY-3 satellite has been in operation since 9 January 2012. ZY-3 satellite is equipped with three-line scanners, nadir (NAD), backward (BWD), and forward (FWD) views and provides worldwide coverage being suitable for applications such as the creation of maps on a scale of 1:50000 and the updating of the maps on a 1:25000 scale (Chen et al, 2015, Tang et al, 2015. This paper presents an approach to generate the RPCs for ZY-3 imagery from RSM.…”
Section: Introductionmentioning
confidence: 99%
“…As a relatively new optical system, the Ziyuan-3 (ZY-3) satellite has been in operation since 9 January 2012. ZY-3 satellite is equipped with three-line scanners (nadir, backward, and forward views) and provides worldwide coverage being suitable for applications such as the creation of maps on a scale of 1:50000 and the updating of the maps on a 1:25000 scale (Chen et al, 2015, Tang et al, 2015.…”
Section: Introductionmentioning
confidence: 99%